2004
DOI: 10.1038/sj.bmt.1704512
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal thrombotic microangiopathy after allogeneic bone marrow transplantation: a clinical imitator of acute enteric graft-versus-host disease

Abstract: Summary:Thrombotic microangiopathy after bone marrow transplantation (post-BMT TMA) is a serious transplantrelated complication. We identified 16 patients with TMA after allogeneic BMT who showed histopathological evidence of intestinal TMA in their gut specimens (six autopsies, 10 biopsies). In all, 14 patients had grade II-IV acute graft-versus-host disease (GVHD). The first seven patients were retrospectively diagnosed with TMA. Since six of them were diagnosed with progressive GVHD at that time because the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 30 publications
3
84
0
Order By: Relevance
“…17,18 As one reason for refractoriness to immunosuppressive treatment, we reported for the first time that intestinal tract was also a target organ for TAM. 19 Intestinal TAM (i-TAM) developed as ischemic colitis in some of the patients suffering from severe diarrhea after transplantation. Although clinical symptoms such as abdominal pain and severe and bloody diarrhea resemble those caused by intestinal GVHD, i-TAM can be diagnosed histopathologically by means of colonoscopic biopsies even for patients who do not meet the clinical criteria of systemic TAM.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 As one reason for refractoriness to immunosuppressive treatment, we reported for the first time that intestinal tract was also a target organ for TAM. 19 Intestinal TAM (i-TAM) developed as ischemic colitis in some of the patients suffering from severe diarrhea after transplantation. Although clinical symptoms such as abdominal pain and severe and bloody diarrhea resemble those caused by intestinal GVHD, i-TAM can be diagnosed histopathologically by means of colonoscopic biopsies even for patients who do not meet the clinical criteria of systemic TAM.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of mPSL to Tac and sMTX strongly suppressed acute GVHD in unrelated donor BMT but not chronic GVHD [35]. It has been suggested that calcineurin inhibitors are involved in the development of intestinal thrombotic microangiopathy, a life-threatening complication after allogeneic transplantation, in humans and rats [38][39][40]. The blood concentration of Tac was not necessarily high in patients who developed Tac-related encephalopathy [41].…”
Section: Tacrolimus (Tac)-based Regimensmentioning
confidence: 92%
“…Their causes of death were relapse (n ¼ 5), graft failure (n ¼ 4), ES (n ¼ 1), posterior reversible encephalopathy syndrome (n ¼ 1), sinusoidal obstruction syndrome (n ¼ 1), intestinal TAM 21,22 (n ¼ 2), and infection (n ¼ 2). Of 47 patients in the non-HP group, 14 died.…”
Section: Causes Of Deathmentioning
confidence: 99%
“…Potential prognostic factors considered in the analysis were recipient age, disease risk, hematopoietic cell transplantation-specific comorbidity index, 20 HLA disparity in the GVH direction in HLA-A, -B, -C, -DRB1 alleles, donor type (related or unrelated), donor-recipient sex-match, conditioning regimen, SC source, GVHD prophylaxis, total number of hemophagocytic cells in BM clot sections on day þ 14 ± 7 and presence or absence of documented infections between day þ 7 and day þ 21. ES, sinusoidal obstruction syndrome, intestinal transplant-associated microangiopathy (intestinal TAM), 21,22 and posterior reversible encephalopathy syndrome were categorized as endothelial complications, as they are caused by vascular endothelial damage. 4,5,[21][22][23][24][25] P-values of less than 0.05 were considered statistically significant.…”
Section: Statistical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation